Molecular typing and in vitro resistance of Cryptococcus neoformans clinical isolates obtained in Germany between 2011 and 2017 - Selb, Regina; Fuchs, Vidmante; Graf, Barbara; Hamprecht, Axel; Hogardt, Michael; Sedlacek, Ludwig; Schwarz, R.; Idelevich, Evgeny A.; Becker, Sören L.; Held, Jürgen; Küpper-Tetzel, Claus P.; McCormick-Smith, Ilka; et al. (International Journal of Medical Microbiology, 2019)
Cryptococcosis is a fungal infection of the central nervous system predominantly caused by Cryptococcus neoformans in immunocompromised patients. In several countries worldwide, up to 50% of isolates show in vitro resistance to clinically used antifungals including fluconazole. No prospective data on susceptibility to antifungal drugs are available for Germany. In this study, we characterised all C. neoformans isolates collected from individual patients’ samples at the German reference laboratory for cryptococcosis 2011 and 2017 (n = 133) by multi-locus sequence typing and phenotypic drug susceptibility testing. We identified serotype A/genotype VNI isolates belonging to clonal complexes previously described from Europe, Africa, Asia and South America as the most prevalent agents of cryptococcosis in Germany. Overall, we observed minimal inhibitory concentrations (MICs) above the epidemiological cut-offs (ECVs) in 1.6% of isolates regarding fluconazole and 2.3% of isolates regarding 5-flucytosine. Here, two C. neoformans var. grubii isolates displayed decreased drug susceptibility to fluconazole, one of them additionally to 5-flucytosine. We also found 5-flucytosine MICs above the ECV for two C. neoformans var. neoformans isolates. We identified a novel mutation in the ERG11 gene which might be associated with the elevated fluconazole MIC in one of the isolates. The clinical importance of the detected in vitro resistance is documented by patient histories showing relapsed infection or primary fatal disease. Of note, sertraline demonstrated antifungal activity comparable to previous reports. Systematic collection of susceptibility data in combination with molecular typing of C. neoformans is important to comprehensively assess the spread of isolates and to understand their drug resistance patterns.
CRIS-Team Scopus Importer:2019-08-30
Keywords: Cryptococcosis; Cryptococcus neoformans; Fluconazole; Flucytosine; Fungal drug resistance; MLST